Examining the stability and specificity of pattern recall in team handball - Raab, M.; Farrow, D. (International Journal of Sport Psychology, 2015)
The aim of this study was to test the stability and specificity of pattern recall in team handball over the course of development. An ecological rationality framework of human behavior was used that allowed predictions of pattern recall specialization over the development of athletes in different positions of play. In a longitudinal study fifty team handball players were assigned to three expertise groups in three phases in which they were asked to recall patterns of play on a computer representing familiar situations. Results indicated expertise effects for pattern recall. Recall was more specific to players` playing position and an interaction between the specificity of recall and testing phases indicated an adaptation of recall performance. It is argued that pattern recall performance is an important aspect of expertise development that adapts over the course of development to the information related to the specific position played. Further research is needed to evaluate how training can moderate such developmental trends.